Reduced Expression of Cerebral Metabotropic Glutamate Receptor Subtype 5 in Men with Fragile X Syndrome - Brašić, James R.; Nandi, Ayon; Russell, David S.; Jennings, Danna; Barret, Olivier; Mathur, Anil; Slifer, Keith; Sedlak, Thomas; Martin, Samuel D.; Brinson, Zabecca; Vyas, Pankhuri; Seibyl, John P.; et al. (Brain sciences, 2020)
Glutamatergic receptor expression is mostly unknown in adults with fragile X syndrome (FXS). Favorable behavioral effects of negative allosteric modulators (NAMs) of the metabotropic glutamate receptor subtype 5 (mGluR5) in fmr1 knockout (KO) mouse models have not been confirmed in humans with FXS. Measurement of cerebral mGluR5 expression in humans with FXS exposed to NAMs might help in that effort. We used positron emission tomography (PET) to measure the mGluR5 density as a proxy of mGluR5 expression in cortical and subcortical brain regions to confirm target engagement of NAMs for mGluR5s. The density and the distribution of mGluR5 were measured in two independent samples of men with FXS (N = 9) and typical development (TD) (N = 8). We showed the feasibility of this complex study including MRI and PET, meaning that this challenging protocol can be accomplished in men with FXS with an adequate preparation. Analysis of variance of estimated mGluR5 expression showed that mGluR5 expression was significantly reduced in cortical and subcortical regions of men with FXS in contrast to age-matched men with TD.